THE ROLE OF DEPOSIT POLICY IN EXPANDING THE BANK'S DEPOSIT BASE - Akmaljon Anvarjonovich Mamatov (Scholars Digest Publishing, 2023)
Annotation. In the article, the main directions of the deposit policy of commercial banks, as well as the processes and principles of its formation, are studied in detail from a theoretical and practical point of view. Also, proposals were made to increase the role of deposit policy in expanding the deposit base of commercial banks.
Keywords: Commercial bank, deposit, deposit policy, population savings, bank resources, attracted funds.